Experiencing place identity: A phenomenological study of visitor perception in old Jeddah - AlGhunaim, Jory; Saputra, Irfan Adi; Rahmani, Ahmad Ridho (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: Jeddah (Al-Balad), a UNESCO World Heritage Site, embodies a rich tapestry of cultural and architectural heritage that shapes its unique place identity. Methods: This study explores the phenomenological experience of visitors to Old Jeddah, focusing on how sensory perceptions and spatial interactions contribute to their understanding of place identity. By employing a mixed-method approach combining in-depth interviews and on-site observations, this research uncovers the nuanced ways in which visitors engage with the physical and intangible heritage of Al-Balad. Findings: The findings reveal three primary dimensions of visitor experience that enhance place identity: spatial nostalgia, where historical architecture evokes memories and emotional ties; sensory layering, wherein the interplay of sights, sounds, and smells enriches the cultural narrative; and interactive belonging, where participatory activities, such as heritage tours or artisan workshops, foster a deeper sense of connection. A key novelty lies in demonstrating how these sensory and spatial dimensions collectively form a dynamic and evolving sense of place identity, distinguishing Old Jeddah from other heritage sites. Conclusion: This study contributes to heritage literature by bridging phenomenology and place identity theory, while providing actionable insights for policymakers and conservationists to design visitor-centered interventions that strengthen cultural preservation and engagement. Novelty/Originality of this article: By prioritizing authentic, multisensory experiences, this research highlights the potential of Old Jeddah to remain a living heritage site that resonates across generations.